Diesel Fuel Degradation Activity of Hydrocarbon-Degrading Bacteria from Nusantara Fisheries Port Brondong Lamongan - Mahbubillah, M. Ainul; Tamam, Muhammad Badrut; Ayuni, Rieke Dwi; Savitri, Nynda Ayu Nadira; Ramadani, Aisyah Hadi (Program Studi Pendidikan Biologi, 2025)
The Nusantara Fisheries Port (Pelabuhan Perikanan Nusantara - PPN) in Brondong, Lamongan Regency, is a port with high ship activities. This has led to hydrocarbon pollution in the form of diesel fuel and oil in the waters of PPN Brondong. The initial effort to address this pollution is by isolating and characterizing hydrocarbon-degrading bacteria present in these waters. This research is a strategic step in managing petroleum hydrocarbon spills in the area through bioremediation processes, either via bioaugmentation or biostimulation for further study. The research method involves isolating hydrocarbon-degrading bacteria from the waters of PPN Brondong using the spread plate isolation method. Different colony characteristics are selected for the purification of bacterial isolates. The obtained bacterial isolates are then subjected to hydrocarbon degradation activity by culturing them in a minimal medium containing diesel fuel. The degradation activity is measured using total petroleum hydrocarbon (TPH) testing. The results of this study yielded 7 different isolates from the fuel oil-contaminated sites in PPN Brondong. Culturing in a minimal medium containing diesel fuel yielded results showing that all isolates possess the ability to degrade hydrocarbons, as evidenced by the reduction in TPH.